ANALISIS ARKETIPE TOKOH DALAM NOVEL KKPK LONDON I’M COMING KARYA NALA ALYA FARADISA - Laily, Norfil (Jurnal Pena Indonesia, 2016)
Every literary work has a character figure with different properties and unique. Character or personality can be seen from the pattern of behavior. Characters in the novel can be seen from the way the authors describe patterns of behavior or some are directly explain the nature of each character. The pattern of behavior which have on every character in a novel that will be discussed meet the concept of archetypes. Of course, analyzing personality archetypes in draft form should use a scalpel in accordance with the method psikologisastra Textual approach, analysis on each character in the novel. The results of this analysis argues that the concept of archetypes is divided into four sections: Persona, anima and animun, Shadow, and self can be met.